2021
DOI: 10.3389/fonc.2021.659661
|View full text |Cite
|
Sign up to set email alerts
|

SUMOylation Wrestles With the Occurrence and Development of Breast Cancer

Abstract: Breast cancer has the highest incidence among cancers and is the most frequent cause of death in women worldwide. The detailed mechanism of the pathogenesis of breast cancer has not been fully elucidated, and there remains a lack of effective treatment methods for the disease. SUMOylation covalently conjugates a large amount of cellular proteins, and affects their cellular localization and biological activity to participate in numerous cellular processes. SUMOylation is an important process and imbalance of SU… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 111 publications
(158 reference statements)
0
4
0
Order By: Relevance
“…The identified pathways and their frequencies are illustrated in Figure 5. For TCGA-BRCA, evidence of association with breast cancer or cancer in general can be found for all the identified pathways in previous literatures [39][40][41][42][43][44][45][46][47][48]. The pathway with frequency three in Figure 5a, R-HSA-163560, is triglyceride catabolism.…”
Section: Risk Group Assignment and Deepshap Interpretationmentioning
confidence: 63%
“…The identified pathways and their frequencies are illustrated in Figure 5. For TCGA-BRCA, evidence of association with breast cancer or cancer in general can be found for all the identified pathways in previous literatures [39][40][41][42][43][44][45][46][47][48]. The pathway with frequency three in Figure 5a, R-HSA-163560, is triglyceride catabolism.…”
Section: Risk Group Assignment and Deepshap Interpretationmentioning
confidence: 63%
“…SUMOylation is a dynamic process regulated by a family of SUMO-specific proteases called sentrin-specific protease (SENP), which reversely detaches SUMO molecules from the target proteins [ 15 , 16 ]. Among the six members of the SENP family, it was reported that SENP1 plays a critical role in coordinating developmental angiogenesis by affecting the SUMOylation of VEGFR2 and NOTCH1 [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Different from the ubiquitination mediated targets degradation (mainly referring to K48-linked ubiquitin chains), SUMOylation predominantly regulates protein localization and activity, and involves in multiple important biologic functions including cell cycle control, gene expression, genome stability, and protein trafficking, which are important for cell and tissue homeostasis. In recent years, many research groups, including our group, have shown that SUMO signaling is implicated in cancers [ 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 ]. Many different types of cancers show dysregulation of one or more components of the SUMO machinery, which predominantly results in an increase in SUMOylation.…”
Section: Introductionmentioning
confidence: 99%